Study The Impact Of Covid-19 Pandemic Confinement On Body Weight In Young Adults Of 17-18 Yrs In Jaipur (Journal of Pharmaceutical Negative Results, 2023)
Background: The COVID-19 Pandemic hit INDIA in March 2020. This pandemic lead to confinement of students at home for more than a year. This influenced their dietary behaviours and physical activity along with increase in stress levels. The net result of pandemic was alterations in weight, increasing the risk of obesity and diseases associated with obesity especially in affluent class. AIMS and OBJECTIVES: This study aims to evaluate the effect of confinement on body weight in students of 17-18 yrs of Jaipur and to identify the contributory factors.Material and Methods: A school based, cross-sectional, observational study was carried out from January 2021 to june 2021involving 300 students in age group of 17-18 years studying in private school belonging to affluent class. Students were made to fill a proforma regarding their daily lifestyle and physical activities. Physical activity was evaluated with the International Physical Activity Questionnaire. Weight before the pandemic confinement was compared to the post confinement weight. Data was analysed using DATAtab Team (2023). DATAtab: Online Statistics Calculator. DATA tab e.U. Graz, Austria. URL https://datatab.net/ Results: More than 50% of students gained significant weight during the pandemic. Only one third of participants were moderately physically active. Factors contributing to weight gain included increased consumption of unhealthy food, altered sleep pattern, increased screen time and decreased physical activity.Conclusion: The study showed that confinement lead to significant weight gain in students of affluent class .The findings showed the short term effects of pandemic confinement. This study during Covid19 confinement will help the health authorities in understanding and implementing newer policies for healthy lifestyle when newer pandemics waves arrive.